America's Indian Ocean Strategy. Issue 9 (21st October 2017) - Unknown
Abstract : A combination of structural and policy impediments will tend to keep the Indian Ocean region fragmented in the US policy lens. The United States is likely to use the region as a staging area for counter-terrorism efforts in and around the Persian Gulf, and as a secondary theatre in the deepening strategic competition with China. Increasing tension with Iran could also sharpen US focus on the northwest corner of the region.